The Relationship between Mathematics Teachers TPACK and Students' Mathematical Resilience - Anwaril Hamidy; Arista Wibowo (Didaktik Matematika, 2023)
Previous research shows that teachers play a role in determining students' math resilience. However, there is still little research on the type of teacher competencies that support students' mathematical resilience. This study examines the effect of mathematics teachers Technological Pedagogical Content Knowledge (TPACK) on students' math resilience. This quantitative study involved 163 students from a junior high school and four senior high schools in the East Kalimantan region. Data was collected through questionnaires that measured mathematics teachers' TPACK from the student perspective and students math resilience. Information about the gender of respondents is also collected. Data were analyzed using multiple linear regression and moderated regression. The results exposed that the mathematics teachers TPACK significantly affected students' math resilience. The components of Pedagogical Knowledge and Technological Pedagogical Content Knowledge partially affect students' math resilience. However, the study found no moderation by student gender on the relationship between mathematics teachers' TPACK and students' math resilience. This study contributes significantly to understanding the role of mathematics teachers' TPACK in improving students' math resilience. The results can be a reference for related parties, especially in developing more effective mathematics teacher training and competency development programs.